Morbidity and Mortality in Patients Undergoing Coronary Artery Bypass Surgery With and Without Acute Myocardial Infarction - Talledo Quaglino, Oscar (2025)
Objective: To compare morbidity and mortality in patients undergoing coronary artery bypass graft (CABG) surgery with acute myocardial infarction (AMI) and electively (non-AMI). Methods: Retrospective cohort study. Medical records of 237 patients who underwent CABG for three-vessel and/or left main disease were reviewed. 63 patients had surgery during AMI, and 174 had elective surgery. Morbidity and mortality were compared during the hospital stay or within 30 postoperative days. Results: Clinical characteristics were similar in both groups. Operative mortality was higher in the AMI group (7.94% vs. 1.15%, p = 0.006). Common postoperative complications in the AMI group were: stroke (7.94% vs. 0.57%, p = 0.001), reoperation for bleeding (6.35% vs. 1.15%, p = 0.024), and acute kidney injury (15.2% vs. 3.5%, p = 0.009). Conclusions: CABG during AMI in patients with three-vessel/left main disease was associated with more frequent neurological complications, reoperations for bleeding, transient acute kidney injury, and higher mortality compared to elective surgery.